Artificial Wetlands as Breeding Habitats for Shorebirds: A Case Study on Pied Avocets in China’s Largest Saltpan Complex - Lei, Weipan; Wu, Yang; Wu, Fuxing; Piersma, Theunis; Zhang, Zhengwang; Masero, José A. (Frontiers in Ecology and Evolution, 2021)
Artificial wetlands such as saltpans have replaced some of the lost natural intertidal habitat and may have accommodated particular migratory shorebird species in the East Asian-Australasian Flyway. Amongst those, the Nanpu Saltpans, north of Bohai Bay, China, is one of the largest saltpan complexes in the world. To answer the question whether such areas could also have benefited breeding waterbirds, in this study we monitored nesting success (853 nests; the fate of 805 was known) of pied avocets Recurvirostra avosetta during three breeding seasons (2015, 2016, and 2018) in the Nanpu Saltpans. Daily survival rate was 0.970, and hence nest survival during 27 exposure days was 44%. The apparent nest success of three years was 51%. Surprisingly, 55% of the failed nests happened during laying period. Flooding (41%) and nest abandonment (32%) were the main reason for nest failure during both the laying and incubation phases. The nest survival highly varied among the breeding ponds, but not among habitats and years. We show that daily survival rate of nests decreased in the course of the season, and increased with nest age, with lowest at the start and slightly declined at the end of incubation. Nest failure also decreased in denser colonies and during rainfall and human disturbance. Compared with pied avocets nesting in either artificial or natural wetlands, nest survival in the Nanpu Saltpans was rather average. Conclusion to the question whether artificial habitats can offer breeding space: YES!